Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/ijerph17176433
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia in Relation to Academic Performance, Self-Reported Health, Physical Activity, and Substance Use Among Adolescents

Abstract: Purpose: Insomnia affects up to one in four adolescents and has been shown to have a negative impact on their mental and physical health. This study aimed to investigate the association between insomnia, academic performance, self-reported health, physical activity, school start time, and substance use among adolescents. Methods: A survey with a cross-sectional design was completed by adolescents (15–17 years old; n = 1504) in southern Sweden. The Minimal Insomnia Symptoms Scale (MISS) was used to operationali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
(43 reference statements)
0
11
0
Order By: Relevance
“…Results published by Short et al proved that insufficient sleep is associated with 1.43 times greater odds of risky behaviors taken by adolescents, such as enhanced alcohol and drug use, increased violent behavior, including sexual risk, transport risk and others [49]. Another study on adolescents conducted by Hedin et al showed that insomnia was associated with male gender, poor financial situation of a family and self-reported health, low physical activity and higher use of alcohol and/or cigarettes per month [50]. On the other hand, all these behaviors, as well as computer use (and evening light), may be related to sleep latency at this age [51].…”
Section: Discussionmentioning
confidence: 99%
“…Results published by Short et al proved that insufficient sleep is associated with 1.43 times greater odds of risky behaviors taken by adolescents, such as enhanced alcohol and drug use, increased violent behavior, including sexual risk, transport risk and others [49]. Another study on adolescents conducted by Hedin et al showed that insomnia was associated with male gender, poor financial situation of a family and self-reported health, low physical activity and higher use of alcohol and/or cigarettes per month [50]. On the other hand, all these behaviors, as well as computer use (and evening light), may be related to sleep latency at this age [51].…”
Section: Discussionmentioning
confidence: 99%
“…Health and learning are intimately connected. Several studies have shown a connection between students’ health and their school performance, for example, in the case of long-term pain ( Ragnarsson et al, 2020 ) and sleep problems ( Hedin et al, 2020 ).…”
Section: Discussion Of Topicmentioning
confidence: 99%
“…In addition, having chronic health conditions like asthma, mental health diagnosis, and attention disorders during kindergarten to secondary is negatively associated with attendance and grade point average [8]. Appropriated sleep is essential for ensuring a good health since differences in sleep timing like bed time, rise time, mid-point of sleep and sleep duration in school-age children and youths show associations with low academic performance, depressive symptoms, high risk of substance use, overweight/obesity, behavioral problems and suicidality [9,10]. From preschool age the first predictor of school failure and health outcomes maybe absenteeism.…”
Section: Health Impact On Performancementioning
confidence: 99%